On Jacobi Polynomials Of Several Variables - Shrivastava, H.S.P. (Integral transforms and special functions, 2000)
The aim of the present paper is to define the Jacobi polynomial of two variables, three variables and m-variables. Their integral representations, generating functions are obtained. Sokme relationships are established and finally Ultraspherical polynomials, Gegenbauer polynomials, Legendre's polynomials and chebyshev polynomials of m-variables are also defined as a particular cases